Language Learning Approaches: A Study Meta-Analysis of Vocabulary Mastery in EFL Learners - Afini, Vivin; Suratni, Suratni; Cyintia Kumalasari; Fitri Novia; Purwanto, Muhammad Bambang (Journal of Language Development and Linguistics, 2023)
This study does a meta-analysis of three study programs to examine the applicability of the various strategies and methodologies suggested in this research project related vocabulary learning or lexical knowledge. The results demonstrated that the learners' lexical knowledge strategies encompassed cognitive, metacognitive, social, willpower, and memory techniques. Additionally, this study looked into the relationship between the background, circumstance, approach, context, and therapy using a vocabulary acquisition strategy. The findings indicated that while the instructors used particular teaching methods in accordance with their curricula and preferred distinct methods, the L2 beginners came from diverse backgrounds and situations. The study's findings suggest that in order to effectively encourage Instructors at STKIP Muhammadiyah Pagaralam should be well aware of the significance of employing proper techniques of teaching English (ELT) to new EFL students in order to develop their vocabulary.